Factors affecting the development of 1,1,6-trimethyl-1,2-dihydronaphthalene in Vitis vinifera L. cv. Weisser Riesling grapes and wine - Marais, J.(Johann) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D) -- University of Stellenbosch, 1991.